ON A REPRESENTATION OF THE RIEMANN ZETA FUNCTION - Mkrtchyan, Ye.S. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2016)
In this paper a new representation of the Riemann function in the disc U(2,1) is obtained:ζ (z) = 1z-1 + _n=0^∞(-1)^nα_n(z-2)^n, where the coefficients α_k are real numbers tending to zero. Hence is obtained γ=_m→∞[_k=0^nζ^(k)(2)k!-n], where γ is the Euler-Mascheroni constant.